Exploring students\' behavioural patterns during online peer assessment from the affective, cognitive, and metacognitive perspectives: a progressive sequential analysis - Cheng, Kun-Hung; Hou, Huei-Tse (My University, 2015)
Previous research regarding peer assessment has investigated the relationships between peer feedback and learners\' performance. However, few studies investigate in-depth learning processes during technology-assisted peer assessment activities, particularly from affective, cognitive, and metacognitive perspectives. This study conducts a series of quantitative content analyses and progressive sequential analyses to explore 65 university students\' behavioural transition patterns from the three perspectives when they engage in an online peer assessment over two weeks. The findings show that the students mostly offer positive affective feedback but offer relatively less cognitive or metacognitive feedback. As the activity progresses, they increasingly display cognitive and metacognitive thinking in their feedback as well as increased negative affective feelings. While cognitive-oriented and metacognitive-oriented feedback is frequently provided to the groups who performed better, feedback for the groups who performed worse revealed more questions about direction. Further instructional guidance and system design suggestions are proposed for the implementation of online peer assessment.
Keywords: peer feedback; behavioural patterns; content analysis; sequential analysis; online peer assessment